Genetic Diversity of the Q Fever Agent, Coxiella burnetii, Assessed by Microarray-Based Whole-Genome Comparisons - Beare, Paul A. (American Society for Microbiology, 2006)
Coxiella burnetii, a gram-negative obligate intracellular bacterium, causes human Q fever and is considered a potential agent of bioterrorism. Distinct genomic groups of C. burnetii are revealed by restriction fragment-length polymorphisms (RFLP). Here we comprehensively define the genetic diversity of C. burnetii by hybridizing the genomes of 20 RFLP-grouped and four ungrouped isolates from disparate sources to a high-density custom Affymetrix GeneChip containing all open reading frames (ORFs) of the Nine Mile phase I (NMI) reference isolate. We confirmed the relatedness of RFLP-grouped isolates and showed that two ungrouped isolates represent distinct genomic groups. Isolates contained up to 20 genomic polymorphisms consisting of 1 to 18 ORFs each. These were mostly complete ORF deletions, although partial deletions, point mutations, and insertions were also identified. A total of 139 chromosomal and plasmid ORFs were polymorphic among all C. burnetii isolates, representing ca. 7% of the NMI coding capacity. Approximately 67% of all deleted ORFs were hypothetical, while 9% were annotated in NMI as nonfunctional (e.g., frameshifted). The remaining deleted ORFs were associated with diverse cellular functions. The only deletions associated with isogenic NMI variants of attenuated virulence were previously described large deletions containing genes involved in lipopolysaccharide (LPS) biosynthesis, suggesting that these polymorphisms alone are responsible for the lower virulence of these variants. Interestingly, a variant of the Australia QD isolate producing truncated LPS had no detectable deletions, indicating LPS truncation can occur via small genetic changes. Our results provide new insight into the genetic diversity and virulence potential of Coxiella species.